EVALUASI KARAKTER PERTUMBUHAN DAN KOMPONEN HASIL 8 KLON TANAMAN TEBU (Saccharum officinarum L.) DI LAHAN HOLLYWOOD GRESIK - kartika larasati; Setyo Budi (Journal of Agro Plantation (JAP), 2023)
Identification of plants is a process of identifying plants to find out the types of plants in detail and complete and scientifically justifiable. The purpose of this study was to determine the differences in characterization of 8 sugarcane clones and sugarcane clones that had good growth. The research was carried out at the Muhammadiyah Gresik Hollywood University Experimental Garden, Klangonan Village, Gresik at an altitude of 56 meters above sea level (masl). The time for conducting the research was from April to July 2022. This study used a Randomized Block Design (RBD) with one factor, namely 8 types ofclones including: Clones SB27,SB28,SB30,SB31,SB32,SB33, SB34, SB Green,SB200. Each treatment plot clone was repeated 3 times so that there were 27 trial plots. Data analysis used ANOVA with a 5% F test. If there is a significant difference, proceed with 5% DMRT analysis, correlation test, heritability. Morphological data was processed by analyzing plant descriptions. If there is a significant difference, proceed with 5% DMRT analysis, correlation test, heritability. Morphological data was processed by analyzing plant descriptions. The high category of heritability and genetic progress was seen in the stem height (20.55%), cane weight (41.45%), and the brix value was moderately high (5.92%)